Nanoparticle production with stirred-media mills: Opportunities and limits - Knieke, Catharina; Carola, Steinborn; Romeis, Stefan; Peukert, Wolfgang; Breitung-Faes, Sandra; Kwade, Arno (Chemical Engineering & Technology, 2010)
Nanoparticles can be produced by wet grinding in stirred-media mills. In the lower nanometer range a true grinding limit exists, where the transferred energy from the grinding media is no longer sufficient to induce further breakage of the particles even after stressing events with high stress energies. Variations in process conditions lead to the conclusion that the grinding limit is hardly affected by most of the investigated process parameters. However, at high solids concentrations and/or small particle sizes, a drastic increase in suspension viscosity occurs, which leads to a dampening of the grinding media motion and to a reduction in the transferred stress energy. Hence, the rheological behavior can limit the grinding process, and a viscous dampening-related grinding limit can be reached prior to the true grinding limit. © 2010 WILEY-VCH Verlag GmbH & Co.
Keywords: Grinding limit; Nanoparticles; Rheology; Stirred-media mill; Ultrafine grinding